A new species of Leptogorgia (Cnidaria: Anthozoa: Octocorallia) from Golfo Dulce, Pacific, Costa Rica - Breedy, Odalisca; Guzman, Hector M. (Zootaxa, 2012)
The description of this single species is necessary to facilitate the publication of ongoing research conducted by Rita Vargas at the Museum of Zoology, University of Costa Rica, dealing with the associated microfauna. Presently 24 species of Leptogorgia have been reported for the eastern Pacific, 13 of which have been found in Costa Rica (Breedy & Cortés 2011). Although octocoral surveys have been conducted as part of biodiversity studies, there is no published information regarding the occurrence of this taxon in Golfo Dulce. Here we describe a new species of Leptogorgia and compare it with other Leptogorgia species with similar characteristics. Golfo Dulce is a bay located on the southern Pacific coast of Costa Rica. It is about 50 km long, 10–15 km wide, and covers an area of approximately 680 km². The inner part of Golfo Dulce has a maximum depth of slightly over 200 m with a 60 m deep sill at the opening to the Pacific Ocean (Cortés 1999). It has been considered a tropical fjord because of the bathymetry and the presence of anoxic deep waters (Cortés 1999, Svendsen et al. 2006). Specimens were collected by Scuba diving, preserved in 70% ethanol or air dried, and treated and identified following the current methodology (Breedy & Guzman 2002). The holotype and paratypes are deposited in the Museo de Zoología, Universidad de Costa Rica (MZUCR, formerly UCR), San José, P.O. Box 11501-2060, Costa Rica.